Rapid generation of markerless recombinant MVA vaccines by en passant recombineering of a self-excising bacterial artificial chromosome. - Cottingham, MG; Gilbert, S (2010)
The non-replicating poxviral vector modified vaccinia virus Ankara (MVA) is currently a leading candidate for development of novel recombinant vaccines against globally important diseases. The 1980s technology for making recombinant MVA (and other poxviruses) is powerful and robust, but relies on rare recombination events in poxviral-infected cells. In the 21st century, it has become possible to apply bacterial artificial chromosome (BAC) technology to poxviruses, as first demonstrated by B. Moss' lab in 2002 for vaccinia virus. A similar BAC clone of MVA was subsequently derived, but while recombination-mediated genetic engineering for rapid production was used of deletion mutants, an alternative method was required for efficient insertion of transgenes. Furthermore "markerless" viruses, which carry no trace of the selectable marker used for their isolation, are increasingly required for clinical trials, and the viruses derived via the new method contained the BAC sequence in their genomic DNA. Two methods are adapted to MVA-BAC to provide more rapid generation of markerless recombinants in weeks rather than months. "En passant" recombineering is applied to the insertion of a transgene expression cassette and the removal of the selectable marker in bacteria; and a self-excising variant of MVA-BAC is constructed, in which the BAC cassette region is rapidly and efficiently lost from the viral genome following rescue of the BAC into infectious virus. These methods greatly facilitate and accelerate production of recombinant MVA, including markerless constructs.